Analysis of the Content of Religion-Based Identity Politics Branding for the 2024 North Sumatra Gubernatorial Election on Social Media - Akbar Aldi Kautsar; Hasan Sazali; Afwan Syahril Manurung (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study aims to analyse how religious identity is used as a political branding strategy in the 2024 North Sumatra gubernatorial election, and the communicative and social implications of this practice in the digital space. Using a qualitative content analysis, this study examined the official accounts of candidate pairs, digital volunteers, political influencers, and public conversations across various forms, including images, campaign videos, captions, tweets, comments, and hashtags. The results of the study show that religion-based identity politics is the dominant strategy in social media. Candidates and campaign teams actively utilise religious symbols, narratives, and figures to build a religious, trustworthy, and moral image. The endorsement of religious figures through digital testimonials strengthens the candidate's moral legitimacy, while religion-based content is disseminated not only top-down by official accounts but also horizontally through supportive communities and anonymous accounts. Religious content has been shown to have higher digital engagement than neutral content; however, it has also led to polarisation in the commentary space over the legitimacy of using religious symbols in politics.